Developments in the commodity composition, market distribution, and competitiveness of Italy’s foreign trade, 1955-1963 - STERN, R.M. (PSL Quarterly Review, 2014)
<!--[if gte mso 9]> 72 1024x768 <![endif]--> Italy’s foreign trade increased spectacularly in the decade ending in 1963, a major factor contributing to its rapid economic growth in this period. However, following this period a new set of conditions emerged, resulting in an easing in the external payments situation. 1963 thus appears to mark a turning point in the rate and pattern of Italy’s economic growth. The present paper analyses this shift by reviewing the major developments that have occurred in foreign trade in the preceding years. The author determines the contributions to changes in total Italian exports which may be attributable to changes in the commodity composition, market distribution, and competitiveness of these exports. In addition, imports are examined with particular reference to changes in their commodity composition and regions of origin. JEL: F10, O52 <!--[if gte mso 9]> Normal 0 14 <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0pt 5.4pt 0pt 5.4pt; mso-para-margin:0pt; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman";} --> <!--[endif] -->